“Fattened by Friendship” of the Papuan Sawi Tribe: Creative Process and Analysis - Leunupun, Sepnath Yambres; Untung, Rachel Mediana; Soesila, Poedji (Institut Seni Indonesia Yogyakarta, 2025)
“Fattened with Friendship” is the title for the creation of a musical work in the story of Tarop Tim (Child of Peace) of the Sawi Tribe. The creation of this musical work is an effort to contribute to the treasury of Indonesian musical compositions that elevate the cultural values of the Sawi tribe of Papua. The method of music composition creativity applies practice-led research in four creative stages, namely preparation, incubation, illumination and verification. The creation of this new composition elevates the culture of the Papuan Sawi tribe innovatively in melody, rhythm, and other musical elements. The instruments used are string quartet (violin 1-2, alto violin and violoncello), piano, synth, percusion and local Papuan instruments (tifa and pikon). The creation of this musical work aims to be enjoyed by the wider community, especially the younger generation, and to inspire young composers to raise the archipelago’s musical idioms as the foundation of the main creative ideas. “Fattened with Friendship” Suku Sawi Papua: Proses Kreatif dan Analisis. “Fattened with Friendship” merupakan judul dari penciptaan karya musik yang mengangkat kisah Tarop Tim (Anak Damai) dari Suku Sawi. Penciptaan karya musik ini merupakan upaya untuk memberikan kontribusi terhadap khazanah komposisi musik Indonesia yang mengangkat nilai-nilai budaya suku Sawi Papua. Metode penciptaan komposisi musik ini menggunakan metode penelitian yang berbasis praktik dengan empat tahapan kreatif, yaitu persiapan, inkubasi, iluminasi, dan verifikasi. Penciptaan komposisi baru ini mengangkat budaya suku Sawi Papua secara inovatif dalam melodi, ritme, dan elemen musik lainnya. Instrumen yang digunakan adalah string quartet (biola 1-2, biola alto, dan biola cello), piano, synth, perkusi, dan alat musik lokal Papua (tifa dan pikon). Penciptaan karya musik ini bertujuan agar dapat dinikmati oleh masyarakat luas, khususnya generasi muda, dan menginspirasi komposer muda untuk mengangkat idiom-idiom musik nusantara sebagai landasan ide kreatif utama.